Opozorila racionalne zakonodajne politike - Igličar, Albin (Pravnik, 2023)
Legislative policy pertains to setting the goals of legislative activity and determining the ways and means to achieve these goals in the legal regulation of social relations. When the legislator deliberately selects values, goals and means and foresees the consequences, we speak of a rational legislative policy. The triumph of this policy hinges upon an integral view of law, considering both its social function and the personal perception of legal norms by each individual. The fundamental programme document for the management of legislative policy in Slovenia is the Resolution on Normative Activity. It encompasses principles, warnings and numerous yet unrealised objectives. The fundamental ideas of the Resolution must also be taken into account when translating programme documents into legal acts.
Keywords: družbeni odnosi; pravna ureditev; pravne norme; pravo; Resolucija o normativni dejavnosti; zakonodajna politika